Multiscale Analysis of Mechanical Properties and Kinetic Processes in Dry Granular Flow - Ran Xu; Enlong Liu; Jianhe Li (Advances in Civil Engineering)
This study aimed to thoroughly investigate the shear resistance and movement dynamics of dry granular flow by utilizing a discrete element method (DEM) approach. Its focus was on exploring the effects of varying interparticle friction coefficients and slope angles on these processes. A DEM model was developed, integrating critical input parameters such as interparticle friction coefficients and slope angles, to bridge the gap between macro- and mesoscale parameters. The model leveraged complex network theory and the concept of granular temperature to capture the intricate interactions occurring at the mesoscale level. The simulation outcomes, obtained through the use of this model, revealed that shear forces induced particle rearrangement, modifying contact network properties, and disrupting the formation of stable force chains. Furthermore, an innovative macroscopic friction coefficient, tied to granular temperature and mesoscale parameters, was introduced to effectively simulate the movement of dry granular flow. This research provides valuable insights into the dynamic mechanisms underlying dry granular flow by considering the intricate interplay between macro- and mesoscales, utilizing complex network-based parameters, and incorporating granular temperature.